Dampak MEA (Masyarakat Ekonomi Asean) Terhadap Pertumbuhan Ekonomi Indonesia di Era Globalisasi - Alya Adofianti Hermana; Harsya Maulana Fajrin; Yayu Nova Reva; Mohamad Zein Saleh (Universitas 45 Surabaya, 2025)
The ASEAN Economic Community (AEC) is a form of economic integration in the Southeast Asia region which aims to create a single market and joint production base. The aim of this research is to analyze the impact of AEC on Indonesia's economic growth in the era of globalization. The methodology used in this research is a literature review that focuses on economic growth trends before and after the implementation of AEC. The research results show that the MEA has had a positive impact on the Indonesian economy, including increasing exports, foreign investment, and developing strategic sectors such as trade, services, and micro, small and medium enterprises (MSMEs). However, strengthening the competitiveness of local industry and improving the quality of human resources is a big challenge. With the right policies, the AEC can be an opportunity to strengthen Indonesia's position in the global market while simultaneously improving people's welfare in a sustainable manner